Long-term tracing of the BrdU label-retaining cells in adult rat brain. (30th March 2015) - Zhang, Lei; Li, Haihong; Zeng, Shaopeng; Chen, Lu; Fang, Zeman; Huang, Qingjun
Highlights: BrdU pulse-chase method in our study was safe and effective. BrdU-LRCs distributed extensively in brain 24 weeks following BrdU administration. BrdU-LRCs were detected in LV and DG, striatum, cerebellum and neocortex. The highest density of BrdU-LRCs was in lateral ventricle and dentate gyrus. BrdU/GFAP and BrdU/MAP2 double-labeled cells were detected in brain subregions. Abstract: Stem cells have been shown to be label-retaining, slow-cycling cells. In the adult mammalian central nervous system, the distribution of the stem cells is inconsistent among previous studies. The purpose of the present study was to determine the distribution of BrdU-LRCs and the cell types of the BrdU-LRCs in rat brain. To label BrdU-LRCs in rat brain, six newborn rats were administered intraperitoneal injections of BrdU 50 mg/kg/time twice a day at 2 h intervals, over four consecutive days. The BrdU-LRCs were detected by immunohistochemistry, the cell types were examined by double immunofluorescence staining for BrdU/GFAP and BrdU/MAP2, and the percentage of BrdU-LRCs was calculated following a chase period of 24 weeks post-injection. We observed that BrdU-LRCs distributed extensively in rat brain. In the LV, DG, striatum, cerebellum and neocortex, the percentage of BrdU-LRCs was 11.3 ± 2.5%, 10.9 ± 1.3%, 6.4 ± 1.2%, 5.6 ± 0.8%, and 4.9 ± 0.6%, respectively. The highest density of BrdU-LRCs was in LV and DG, the known stem cell sites in adult mammalian brain. Both BrdU/GFAP and BrdU/MAP2 double-staining cells could be detected in the above five brain subregions. Ongoing cell production was widespread in the adult mammalian brain, which would allow us to reevaluate the capacity and potentiality of the brain in homeostasis, wound repair, and regeneration.